1995
DOI: 10.1063/1.868753
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady laminar flow between a pair of disks corotating in a fixed cylindrical enclosure

Abstract: The unsteady streamlined motion of a constant property fluid in the unobstructed space between a pair of disks corotating at angular velocity Ω in a fixed cylindrical enclosure is investigated numerically. Two-dimensional (axisymmetric) and three-dimensional calculations are performed using a second-order accurate time-explicit algorithm. The flow configuration corresponds to that investigated experimentally by Schuler et al. [Phys. Fluids A 2, 1760 (1990)]. The steady flow solutions are characterized by a sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 23 publications
4
45
0
1
Order By: Relevance
“…In that case, rigid-body rotation would be expected to appear in the inner part of the flow. Actually, such a fluid-dynamical system has been investigated in the literature in connection with hard disk drives for computers [30,31,32,33,34]. It has been shown in these studies that most of the fluid rotates rigidly with the disks.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In that case, rigid-body rotation would be expected to appear in the inner part of the flow. Actually, such a fluid-dynamical system has been investigated in the literature in connection with hard disk drives for computers [30,31,32,33,34]. It has been shown in these studies that most of the fluid rotates rigidly with the disks.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In that case, rigid-body rotation would be expected to appear in the inner part of the flow. Actually, such a fluid-dynamical system has been investigated in the literature in connection with hard disk drives for computers [19][20][21][22][23].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The first three-dimensional numerical study of the unsteady flow was published by Humphrey et al [13]. They showed that the toroidal vortices at the shroud "acquire a time-varying sinuous shape in the circumferential direction.…”
Section: A Prior Researchmentioning
confidence: 99%